Odpowiedź :
[tex] \left(\frac{3}{8}x-\frac{1}{4}sin2x+\frac{1}{32}sin4x\right)'=[/tex]
[tex]\frac{3}{8}-\frac{1}{2}cos2x+\frac{1}{8}cos4x=[/tex]
[tex]\frac{3}{8}-\frac{1}{2}cos2x+\frac{1}{8}cos(2\cdot2x)=[/tex]
[tex]\frac{3}{8}-\frac{1}{2}cos2x+\frac{1}{8}(2cos^22x-1)=[/tex]
[tex]\frac{3}{8}-\frac{1}{2}cos2x+\frac{1}{4}cos^22x-\frac{1}{8}=[/tex]
[tex]\frac{1}{4}cos^22x-\frac{1}{2}cos2x+\frac{1}{4}=[/tex]
[tex]\frac{1}{4}(cos^22x-2cos2x+1)=[/tex]
[tex]\frac{1}{4}(1-cos2x)^2=[/tex]
[tex]\frac{1}{4}(1-cos2x)^2=[/tex]
[tex]\frac{1}{4}(1-1+2sin^2x)^2=[/tex]
[tex]\frac{1}{4}(2sin^2x)^2=[/tex]
[tex]\frac{1}{4}\cdot4 sin^4x=sin^4x[/tex]